Puzzles of discourse in being and time: minding gaps in understanding - Baiasu, R (Routledge, 2009)
This paper takes issue with Heidegger's claim that discourse and understanding are equally basic in the constitution of our making sense of the world. I argue that Heidegger cannot consistently establish this claim, and that discourse can be thought of as being more basic than understanding. The proposed line of thinking has the advantage of shedding light on both the finitude and the normativity of our making sense of the world. Thus, by setting up an exchange with the later Wittgenstein's discussion of rule-following makes it possible to develop an approach to the normativity of meaning which was not readily available on Heidegger's account. Further, the paper offers an inquiry into a certain aspect of our finite sense of the world which, in spite of Heidegger's marked attention to finitude, was obscured by his approach to discourse. The implications of the argument might be far-reaching. The view of a basic role of discourse can put into question Heidegger's guiding vision according to which time alone is ultimately the fundamental constituent of our sense of what there is. The engagement with Wittgenstein indicates, in conjuction with other themes of the paper, that there are certain perspectives and issues in phenomenology which are much closer to aspects of the analytic tradition than is usually granted.